Science for Africa’s future food security: rethinking breeding to adapt to diversified cropping systems - Ayenan, Mathieu A. T.; Schafleitner, Roland; Pawera, Lukas; Odjo, Sylvanus (Springer, 2025)
Diversified production systems is a promising strategy to boost productivity, biodiversity, and resilience. Unlocking the potential of diversified cropping systems to improve crop productivity and resilience in Africa requires developing and deploying crop varieties tailored to diverse cropping systems. Achieving this goal hinges on a deep understanding of farmer preferences and their willingness to adopt varieties that boost both productivity and agroecosystem services. A better understanding of existing cropping systems can provide valuable insights for identifying functional traits essential for crop improvement. To effectively harness adaptive and functional traits, breeders, agronomists, physiologists, socio-economists, and farmers must collaborate to select cultivars with desirable characteristics and design optimized production strategies. However, breeding cultivars suited to such systems presents challenges, including the need to identify and select for complex trait combinations, as well as the development of robust phenotyping methods for mixed cropping environments. Addressing these challenges requires innovative breeding techniques, an agroecological understanding of diversified systems, active farmer engagement, supportive institutional, seed, and regulatory policies, and the support of funding agencies, all of which are essential to advancing breeding efforts for diversified systems.